2013
DOI: 10.1073/pnas.1221172110
|View full text |Cite
|
Sign up to set email alerts
|

TAp73 knockout mice show morphological and functional nervous system defects associated with loss of p75 neurotrophin receptor

Abstract: Total and N-terminal isoform selective p73 knockout mice show a variety of central nervous system defects. Here we show that TAp73 is a transcriptional activator of p75 neurotrophin receptor (p75 NTR ) and that p75 NTR mRNA and protein levels are strongly reduced in the central and peripheral nervous systems of p73 knockout mice. In parallel, primary cortical neurons from p73 knockout mice showed a reduction in neurite outgrowth and in nerve growth factor-mediated neuronal differentiation, together with reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…However, we cannot rule out that other transcription factors known to regulate p75 NTR expression might also contribute to p75 NTR deregulation. For instance, it was recently shown that p75 NTR is a direct transcriptional target of the transcriptional activator p73 (Tap73) (71), which has also been demonstrated to be hyperactive in HD mouse models and to play a relevant role in HD pathology (72). Interestingly, hippocampal p75…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot rule out that other transcription factors known to regulate p75 NTR expression might also contribute to p75 NTR deregulation. For instance, it was recently shown that p75 NTR is a direct transcriptional target of the transcriptional activator p73 (Tap73) (71), which has also been demonstrated to be hyperactive in HD mouse models and to play a relevant role in HD pathology (72). Interestingly, hippocampal p75…”
Section: Discussionmentioning
confidence: 99%
“…NTR and Tap73 expression is increased in AD (73,74), suggesting that the p73/p75 NTR axis may also play an important role in the pathology of neurodegenerative diseases (71).…”
Section: Discussionmentioning
confidence: 99%
“…The p73−/− mice also have impaired reflex and neuromuscular function and sensorimotor coordination and increased anxiety. Many of these behavioral abnormalities observed in the p73−/− mice were also found in the TAp73−/− mice [36]. Hippocampal dysfunction is specifically associated with a reduction in burrowing and open field performance [53,54], and the TAp73−/− mice also exhibit a reduction in burrowing and in speed and rearing time in open field tests.…”
Section: P73 Causes Neuronal Development Defectsmentioning
confidence: 84%
“…Accordingly, over 70 % of the TAp73 selective knockout mice (TAp73−/−) show an increased susceptibility to both spontaneous and induced carcinogenesis [34]. In addition, TAp73−/− mice are infertile and exhibit hippocampal dysgenesis, indicating a role for the TAp73 isoform in the regulation of reproduction and in neuronal development [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, TAp73 is necessary for neuronal differentiation and maintenance of neuronal stem cells. [51][52][53][54] Hypoxia inducible factors (HIFs) mediate the physiological response to hypoxia 55 regulating processes, such as angiogenesis, [56][57][58] proliferation [59][60][61][62][63][64][65][66][67][68] and metabolism. 64,[69][70][71][72][73] The wide transcriptional reprogramming operated by HIF-1, includes the direct transcriptional induction of the Bcl-2 Nineteen kilodalton Interacting Protein (BNIP3).…”
Section: Introductionmentioning
confidence: 99%